Perceived body image : selected lifestyle practices and their relationship to physical self-esteem - Norder-Pietrzak, Michelle Marie (My University, 1993)
This study examined physical self-esteem in 302 college age females with special attention to the perceived physical appearance subdomain. Further investigation addressed body image and nutritional and exercise practices which contribute to perceived physical appearance and consequently physical self-esteem. Instruments used for data collection included the Physical Self-Perception Profile (PSPP), the Perceived Importance Profile (PIP), modified Body Silhouette Drawings (BSD), a Physical Activity Inventory (PAI), and a Exercise/Nutrition Trend Questionnaire. The results supported previous findings that women perceive physical appearance as the most important subdomain affecting physical self-esteem. Health and fitness related education positively affected perceived physical self-esteem and perceived importance as shown by the changes in the subscale weightings on the PSPP and PIP. Women ages 18 to 25 years viewed their current body image as being greater in size then their perceived ideal body image. Appropriate activities were chosen that would positively affect physical appearance, but a significant decrease in activity levels was confirmed for women as they age fG2 and G3, increase, t = .90, p < .05; G3 and G4, decrease, t = .70, p 5 - 0 5 ) . Woomen in this study engaged in unhealthy lifestyle practices that could have a negative effect on physical appearance and be detrimental to their health, consequently decreasing their physical self-esteem.
Keywords: Women college students - Health and hygiene - Psychological aspects; Women college students - Psychology; Self-esteem in women; Body image